Eculizumab in Typical Hemolytic Uremic Syndrome (HUS) With Neurological Involvement. Issue 24 (June 2015) - Pape, Lars; Hartmann, Hans; Bange, Franz Christoph; Suerbaum, Sebastian; Bueltmann, Eva; Ahlenstiel-Grunow, Thurid; Munoz., Miguel
<x xml:space="preserve">Abstract</x> Abstract In typical hemolytic uremic syndrome (HUS) approximately 25% of patients show central nervous system (CNS) involvement often leading to serious long-term disabilities. We used the C5-complement inhibitor Eculizumab as rescue therapy. From 2011 to 2014, 11 children (median age 22 months, range 11–175) with enterohemorrhagic Escherichia coli-positive HUS requiring dialysis who had seizures (11/11) and/or were in a stupor or coma (10/11) were treated with Eculizumab. Two patients enrolled on the Safety and Efficacy Study of Eculizumab in Shiga-Toxin Producing E coli Hemolytic-Uremic Syndrome (STEC-HUS) each received 6 doses of Eculizumab, 3 patients 2 doses, and 6 patients 1 dose. Laboratory diagnostics of blood samples and magnetic resonance imaging (MRI) were performed as per center practice. Data were analyzed retrospectively. Cranial MRI was abnormal in 8 of 10 patients with findings in the basal ganglia and/or white matter. A 2-year-old boy with severe cardiac involvement and status epilepticus needed repeated cardio-pulmonary resuscitation and extracorporeal membrane oxygenation. He died 8 days after start of Eculizumab treatment. Two patients with hemorrhagic colitis and repeated seizures required artificial ventilation for 6 and 16 days, respectively. At the time of discharge, 1 patient showed severe neurological impairment and 1 mild neurological impairment. The 8 surviving patients experienced no further seizures after the first dose of Eculizumab. Three patients showed mild neurological impairment at discharge, whilst the remaining 5 showed no impairment. The platelets normalized 4 days (median) after the first dose of Eculizumab (range 0–20 days). The mean duration of dialysis after the first dose of Eculizumab was 14.1 ± 6.1 days. In children with typical HUS and CNS involvement early use of Eculizumab appears to improve neurological outcome. In severe HUS cases which progress rapidly with multiple organ involvement, late treatment with Eculizumab seems to show less benefit. We speculate that prophylactic Eculizumab therapy before development of neurological symptoms could be advantageous.